Pengaruh Model Permainan Tradisional Bentengan Terhadap Hasil Belajar Gerak Dasar Lokomotor Pada Siswa Kelas V Sdn Duri Utara 04 Petang Jakarta Barat - Syifa Fauzia; Bayu Thomi Rizal; Khavisa Pranata; Asruddin Asruddin (Dinasti Review, 2024)
The purpose of this study was to evaluate whether the use of learning models in the Bentengan Traditional Game of class V SDN in Duri Utara 04 Petang has a significant impact on the achievement of student learning outcomes in PJOK subjects. Especially in understanding Basic Locomotor Movements. This research method utilises a quantitative approach with a Quasi Experimental Design in the form of Post Test-Only Control Design. Grade V students from one of the public elementary schools in West Jakarta City became the research sample. The sample was selected using the Random Sampling method. Point Biserial correlation was conducted to test the validity of 40 items, it was found that 25 items were valid, while 15 items were invalid (dropped). While in the Reliability Test, the Alpha Cornbach formula was used, obtained = 0.818> 0.381 = then the data is categorised or qualified as